A Study of Hydrogen Charging of 10M Ni-Mn-Ga Single Crystal. (2015) - Ge, Y.; Aaltio, I.; Hannula, S.P.
Abstract: The effect of hydrogen charging on twinning stress and surface microstructure was investigated in 10 M Ni-Mn-Ga ferromagnetic shape memory alloy. During hydrogen charging on the bulk sample, cross-like pits formed which gradually evolve into diamond shaped cracks on the surface. The cell boundaries are well visible and there is about 20 μm wide area next to the cell boundary is less cracked. The evolution of the microstructure before and after hydrogen charging is also studied by transmission electron microscope (TEM). There is no visible change in the average twinning stress during hydrogen charging even if the surface is dramatically covered with pits and micro cracks.